Examining grid-forming inverters for power restoration using power-hardware in-the-loop and Digital Twins approaches with Real-time Digital Simulation - Chow Jason, Man Hin; Li Ben, Kai Yiu (Frontiers in Energy Research, 2024)
The current pursuit of ambitious decarbonization targets is driving a swift transformation of the power grid, marked by a surge in the production of renewable energy. The expansion on application of renewable energy hinges significantly on Distributed Energy Resources but system operators are grappling with challenges due to the opaque nature of DER operations. This opacity introduces considerable risks to grid stability, as the burgeoning volume of DERs may surpass the existing power network’s capacity. In response, the advent of Digital Twins (DT) technology offers a viable remedy by creating virtual counterparts of the physical grid infrastructure that necessitate transmitting minimal data. Digital Twins technology circumvents the hindrances associated with real-time data flows and bolsters the transparency of the system. To foster widespread implementation of DT within the sector, it is imperative to cultivate and validate its application through practical trials. To this end, Power Hardware-in-the-Loop (PHIL) experiments are employed to juxtapose the efficacy of actual power components against that of the DT models. The experiments involve connecting Grid-forming Inverter to a Real-time Digital Simulator (RTDS) for PHIL and DT testing, allowing for an in-depth analysis of the behaviour of photovoltaic inverter. This paper elucidates a platform engineered for immediate simulation tailored to DT and PHIL approaches. This platform is designed to prototype, exhibit, and evaluate grid-forming inverters under different scenarios that are critical for power restoration. With the help of simulation exchange, Perez Model is recommended to add in the DT model to increase the accuracy comparing with the PHIL model. The entire restoration process can therefore be comprehensively represented and analysed.